QUALITY CONTROL DUE TO DAMAGED RETURNED GOODS AT THE CHANGHONG WAREHOUSE - Putranti, Indah Puspitaning Tyas; Luluk Fauziah (Journal of Economic and Economic Policy, 2025)
Objective: This research aims to describe quality control related to damage in returned goods, identify quality control implementation using the PDCA (Plan-Do-Check-Act) method. Method: To address these issues, the company implemented strategies such as fishbone diagram analysis and the 5 Why analysis, and developed a Work Instruction (WI) as a standard operating guideline to support comprehensive quality control improvements. Results: The results of the study indicate that the primary causes of damage to returned goods include improper use of hand pallets and an overloaded warehouse, leading to limited and inaccessible storage space. In addition, ineffective communication also contributes to the high number of returned goods. Novelty: The company has obtained ISO 9001 certification, which focuses on quality management systems, as evidence of its commitment to implementing quality control standards. However, in practice, the quality control implementation at this company has not been optimal. This is evident from the high rate of damage in returned goods, which exceeds the annual target limit of 90 cartons out of the total returned items received.